SOSIALISASI PENTINGNYA MAHASISWA MAMPU MENULIS KARYA ILMIAH PADA MAHASISWA KIP-KEMENAG STEBIS IGM - Aravik, Havis; Tohir, Ahmad; Nofiansyah, Doly (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
This socialization aims to increase the understanding of KIP-Kemenag recipient students at STEBIS IGM about the importance of scientific writing skills in the academic and professional world. Through this socialization, students are expected to be able to understand the benefits of writing scientific papers in improving academic reputation and career development in the future. This socialization activity was carried out using lecture methods that provide in-depth explanations of scientific writing standards and procedures, question and answer sessions to answer various student questions, and discussions to encourage active participation and share experiences in writing. In addition, an evaluation was conducted to assess students' understanding and ability to plan scientific papers that meet academic standards. The results of the socialization showed increased student awareness of the importance of writing scientific papers as well as a better understanding of the use of supporting tools such as Turnitin and Mendeley. This socialization is expected to help students in completing academic tasks and prepare them for greater contributions in the academic environment in the future